High accumulation of calcium and phosphorus in the pineal bodies with aging - Nutcharin Ongkana (2018)
To elucidate compositional changes of the pineal body with aging, the authors investigated age-related changes of elements in the pineal body. After the ordinary dissection by medical students was finished, the pineal bodies and seven arteries were resected from the subjects ranging in age from 58 to 94 years. The element contents were determined by inductively coupled plasma atomic emission spectrometry. It was found that a high accumulation of Ca and P occurred in the pineal bodies with aging. Regarding the relationships among the elements, it was found that there were significant direct correlations among the contents of Ca, P, and Mg. With regard to the relationships between the pineal body and the arteries, no significant correlations were found in the Ca content between the pineal body and the arteries, such as the thoracic and abdominal aortas and the coronary, common carotid, pulmonary, splenic, and common iliac arteries. © Humana Press Inc. 2007.